Determination of Association between Onychoscopy Features and Nail Plate Potassium Hydroxide Test Positivity in Diagnosis of Onychomycosis: A Cross-Sectional Study - Khubaib Tahir; Sumera Hanif; Rabia Shaukat; Aliza Hamadani; Ayesha Arshad Chattha; Iram Kausar; Haroon Nabi (Pakistan Journal of Health Sciences, 2026)
Onychomycosis is a common chronic fungal infection of the nails, causing significant physical and psychological morbidity. In Pakistan, access to fungal culture and molecular diagnostics is limited, creating a need for non-invasive, rapid, and cost-effective diagnostic tools. Objectives: To determine the association between onychoscopic features and KOH positivity in clinically suspected onychomycosis. Methods: This cross-sectional study was conducted in the Department of Dermatology, Ghurki Trust and Teaching Hospital, Lahore, Pakistan, from 7 August 2025 to 10 January 2026. A total of 52 patients with clinically suspected onychomycosis were enrolled. Each patient underwent onychoscopic examination followed by nail plate potassium hydroxide (KOH) testing for fungal confirmation. Onychoscopic features, including onycholysis, jagged edge with spikes, longitudinal striae, subungual hyperkeratosis, and chromonychia, were documented. Sensitivity, specificity, predictive values, and diagnostic accuracy were calculated for each feature using KOH microscopy as the reference standard. Results: KOH test was positive in 82.7% of cases. Onycholysis had the highest sensitivity (86.1 %) while jagged edge with spikes demonstrated the highest specificity (88.9%). Onycholysis was significantly associated with KOH positivity (p=0.026), and jagged edge with spikes also showed a highly significant association (p=0.002). The combination of jagged edge and onycholysis yielded an accuracy of 76.9%. Chromonychia (p=0.160) and longitudinal striae (p=0.716) showed weaker associations. Conclusions: Specific onychoscopic features, particularly jagged edges with spikes and onycholysis, demonstrated a significant association with KOH positivity. However, given variability in sensitivity and specificity, these findings should be interpreted alongside confirmatory testing (culture or PCR, where available) rather than as standalone diagnostic criteria.